Being epic after Homer: the episodic structure of Quintus of Smyrna’s Posthomerica (Nuntius Antiquus, 2023)
This article investigates the plot structure of Quintus of Smyrna’s Posthomerica, a late antique epic that covers the Homeric lacuna in dactylic hexameters (c. 3 AD). The unmistakable influence of Homer has often led to disparaging views about the quality of Quintus’ poem, which was deemed problematic by many scholars in the 20th Century. After the turn of the century, however, more positive outlooks on the Posthomerica have been gaining momentum, and some previous views have been put into perspective. An explanation for the negative responses elicited by the poem may have to do with an arguable aesthetic of the tension of opposites, here discussed in terms of the poem’s plot, pointing to a “symmetrically asymmetrical” structure. Moreover, the article questions the readily disparaging views against episodic works, which are usually considered lesser pieces in comparison to those with a unified plot.